Innovation networks in different industrial settings : a longitudinal study of northern Sweden and northern Finland - Ylinenpää, Håkan; Teräs, Jukka; Örtqvist, Daniel (Luleå tekniska universitet, Innovation och Design, 2013)
Godkänd; 2013; 20130523 (ysko)